1991
DOI: 10.1073/pnas.88.6.2264
|View full text |Cite
|
Sign up to set email alerts
|

An enhancer variant of Moloney murine leukemia virus defective in leukemogenesis does not generate detectable mink cell focus-inducing virus in vivo.

Abstract: Moloney murine leukemia virus (Mo-MuLV) induces T-cell lymphoma when inoculated into neonatal mice. This is a multistep process. Early events observed in infected mice include generalized hematopoietic hyperplasia in the spleen and appearance of mink cell focus-inducing (MCF) recombinants; end-stage tumors are characterized by insertional proviral activation of protooncogenes. We previously showed that an Mo-MuLV enhancer variant, Mo+PyF101Mo-MuLV, has greatly reduced leukemogenicity and is deficient in induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 20 publications
2
45
1
Order By: Relevance
“…In a separate study (data not shown), at 6 weeks postinfection as neonates with the biologically cloned ecotropic virus, three mice displayed high-level ecotropic MuLV expression in spleen and thymus, and one thymus specimen was positive for MCF MuLV. Thus, as predicted from other studies of exogenous infections (2,13,28), MCF MuLV can be generated in vivo shortly after exogenous infection with CFW ecotropic virus. Induction attempts with cloned ecotropic and MCF viruses will be required to clarify whether both classes, singly or in concert, are lymphomagenic.…”
Section: Resultsmentioning
confidence: 64%
“…In a separate study (data not shown), at 6 weeks postinfection as neonates with the biologically cloned ecotropic virus, three mice displayed high-level ecotropic MuLV expression in spleen and thymus, and one thymus specimen was positive for MCF MuLV. Thus, as predicted from other studies of exogenous infections (2,13,28), MCF MuLV can be generated in vivo shortly after exogenous infection with CFW ecotropic virus. Induction attempts with cloned ecotropic and MCF viruses will be required to clarify whether both classes, singly or in concert, are lymphomagenic.…”
Section: Resultsmentioning
confidence: 64%
“…The gross pathology of the sacrificed animals indicated enlarged thymus, spleen or lymph nodes for animals of all genotypes, characteristic of the lymphoblastic lymphoma induced by M-MuLV in B6 and other mouse strains (Brightman et al, 1991). Molecular diagnosis of the tumors was performed by testing tumor DNAs for rearrangements of T-cell receptor beta (TCRβ), immunoglobulin Mu heavy chain (IgH) and immunoglobulin kappa light chain (IgK) genes.…”
Section: Resultsmentioning
confidence: 99%
“…The origins of the disease-inducing defective component of MAIDS virus as well as MCF virus genomes from endogenous viruses have been well documented (5,7,8,20,29,47). What is the possible origin of the RLMuLV mixture?…”
Section: Discussionmentioning
confidence: 99%